(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
To put into practice the methods of active learning in higher educational institutions, allowing to achieve positive results in the development of artistic and creative abilities of students, as well as to carry out significant work on the development of art education using world experience.